2013
DOI: 10.1590/s0102-695x2012005000109
|View full text |Cite
|
Sign up to set email alerts
|

Spray drying of Eugenia dysenterica extract: effects of in-process parameters on product quality

Abstract: A 2³ full factorial design was used to assess the impact of spraying air flow rate (30-50 L/min), drying air inlet temperature (90-150 ºC) and extract feed rate (4-6 g/min) on the quality of Eugenia dysenterica DC., Myrtaceae, spray-dried extracts. Response surface methodology (RSM) was applied to analyze the significance of the effects of process factors on product quality and to obtain fitted equations to predict dry powder properties. Powder yields were satisfactory, ranging from 34.64 to 63.92%. The dried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 30 publications
3
13
0
1
Order By: Relevance
“…When the temperature elevated from 110 • C to 150 • C, TPC was reduced from 3.02 to 2.12 mg GAE/100 g DW. The highest TPC was achieved at 110 • C and the lowest one was collected at 150 • C. Similar observations were found in a research of Misha et al [34] of which the TPC of amLa juice powder decreased from 250 to 150 mg GAE/100 g DW when spray-drying inlet temperature increased from 125 • C to 175 • C.…”
Section: Total Phenolic Contentsupporting
confidence: 88%
“…When the temperature elevated from 110 • C to 150 • C, TPC was reduced from 3.02 to 2.12 mg GAE/100 g DW. The highest TPC was achieved at 110 • C and the lowest one was collected at 150 • C. Similar observations were found in a research of Misha et al [34] of which the TPC of amLa juice powder decreased from 250 to 150 mg GAE/100 g DW when spray-drying inlet temperature increased from 125 • C to 175 • C.…”
Section: Total Phenolic Contentsupporting
confidence: 88%
“…The analysis of this behavior is widely detailed in the scientific literature [18,23,25,[37][38][39][40]. These results agree with Souza et al [18], in this research the evaporation capacity in SD process depends on the inlet temperature and feed rate (pump setting) and are determining factors in the moisture content of Bauhinia forficata extract.…”
Section: Moisture Contentsupporting
confidence: 86%
“…However, due to an increase in temperature, the response variable produces samples with smaller particle size, possibly due to the evaporation of ethanol before they are formed from larger droplets. Some authors [25,36,39] found similar results.…”
Section: Fig 1: Sem Microphotographs Of Spray Dried P Peruviana Frumentioning
confidence: 53%
See 1 more Smart Citation
“…The lyophilized hydroalcoholic extract (yield: 19.5%, w/w) was obtained through the percolation of leaf powder (1 kg) in ethanol:water solution (70:30, v/v), standardized by determination of its major phytochemical markers (3.45% and 53.7% of tannins and flavonoids, respectively) and used for developing of a product via spray drying, as previously described by our research colleagues (Couto et al 2009(Couto et al , 2011(Couto et al , 2012(Couto et al , 2013.…”
Section: Obtaining Of Edementioning
confidence: 99%